A basic report on the world crude oil outlook : Middle East, North Slope, North Sea, companies: Atlantic Richfield, Phillips Petroleum, Standard Oil (Ohio) - Lewison, Ronald D.; William D. Witter, inc. ([New York : William D. Witter, inc., 1974)
This book examine the crude outlook in selected energy and petroleum companies in Ohio. The book provide statistical graph on how these companies are fed.
asm; 06/03/19
Loans
Keywords: Petroleum industry and trade; Petroleum products